KOMUNIKASIMULTI-LANGUAGEMASYARAKAT PANGKALAN BUN KABUPATEN KOTAWARINGIN BARAT PROVINSI KALIMANTAN TENGAH TERHADAP KEHIDUPAN SOSIAL BERMASYARAKAT - Ananda khoerunnisa; Ardiyanto Wardhana (AKADEMI KOMUNIKASI RADYA BINATAMA, 2022)
This research is to know how does the multi-language communication inPangLalan Bun society towards the harmony of social life. The communication wasborn because of human-thinking and admitting of existence themselves. Ttieexistence was from the admitting of other person. This admittfng was because oflanguage. By using a language, a human being is able to share their opinions, andthe result will be a communication each others. The communication betweenhumans will produce a society. The society that interacted each others will producea new culture.This research is about the multi-language communication in Pangkalan BunTown in the society life by using Qualitative-Descriptive Method. The location ofthis research were in urban village office, and Kuning Palace. The data wascollected by interviewed to The Prince OfAma Muajidinsyah. experts of language,and the leaders of urban village in Pangkalan Bun.The result of this research showed that multi-language communication hadeffected towards the condition and situation in Pangkalan Bun city which havingkind of languages and cultures in every parts of city so that it was able to createintercultural communication. Then. it showed the perception, verbal and non-verbalwhich able to create the assumption of assimilation, separation, integration, andculture hybridity so that it could make the harmony of social life. There were sevenlanguages in Pangkalan Bun city that used to communicate in their daily life then itcould create multi-language based on context, also with whom they are speaking.Now, many citizen could speak more than one language.